Effects of enabling characteristics of budgetary control on the psychological capital of managers with budgetary responsibility - Vinícius Costa da Silva Zonatto; Fernanda Souto Machado; Andson Braga de Aguiar; Luiz Henrique Figueira Marquezan (Revista Contabilidade & Finanças, 2023)
ABSTRACT This study investigates the influence of enabling characteristics of budgetary control on the psychological capital of managers with budgetary responsibility. Within the budgetary context, the studies that analyze the effects of enabling characteristics of budgetary control on individuals’ mental states at work are still in their infancy and that is a theoretical gap explored in this research. The research evaluates the interactive and multidimensional effects of enabling budgetary control on psychological capital. It advances the literature by indicating which characteristics exert the greatest influence on psychological capital and its dimensions. The results provide evidence of the enabling effects of enabling budgetary control on the psychological capacities of managers with budgetary responsibility, being positively reflected in their beliefs of self-efficacy, hope, optimism, and resilience for achieving their objectives and the desired organizational results, which tends to have an impact on the individuals’ as well as the organization’s performance. A survey was conducted in a publicly-traded company operating in Brazil, using a quantitative approach to the data (structural equation modeling). The sample analyzed included 85 middle-level managers from different areas of the organization. The possibility of adjusting budgetary reports and accessing detailed information on budgetary deviations (repair capacity), as well as of incurring expenses unforeseen in the budget and adjusting the original budgetary assumptions (budgetary flexibility), positively contributes to promoting managers’ psychological capital. However, this does not occur with internal transparency and global transparency. Within the context studied, the benefit of repair capacity primarily takes the form of self-efficacy, resilience, and hope, while the benefit of flexibility primarily occurs in terms of optimism and hope. These results contribute to organizations designing their management control systems so as to develop the psychological capital of their collaborators and thus obtain the benefits expected from that development.